Synthesis, characterization and dielectric relaxation study of hyperbranched polymers with different molecular architecture. (25th September 2016) - Giussi, Juan M.; Azzaroni, Omar; Hensel-Bielowka, Stella; Wojnarowska, Zaneta; Knapik, Justyna; Paluch, Marian
Abstract: Hyperbranched polymers are macromolecular systems of high branching density. They play a key role in the forefront of macromolecular synthesis for having features different from those of non-hyperbranched polymers and unique properties that make them amenable for use in a variety of applications. This paper presents the results from the synthesis of hyperbranched polymers of different molecular architecture, i.e., spherical and cylindrical. Also characterization of their thermal and dynamic properties is provided. Atom transfer radical polymerization from star and linear pre-former macroinitiators produced hyperbranched systems based on methyl methacrylate and lauryl methacrylate. Thermal characterizations by TGA and DSC allowed different types of interactions and degradation mechanisms as a function of the determined polymer architecture. NMR studies revealed the effect of molecular architecture on monomers tacticity along the molecular brushes. Spherical architecture yielded a higher isotactic percentage than cylindrical architecture did, thus indicating a specific stereochemistry as a function of the macro-initiator morphology. Broadband dielectric spectroscopy, one of the most powerful techniques to study the dynamics of molecular systems revealed not only different patterns of behavior of hyperbranched polymers of different architectures but also results in agreement with NMR on stereochemistry as a function of molecular architecture. Graphical abstract: Given the structure-property relationships, it is crucial to design macromolecular materials using Hyperbranched Polymers as building blocks. Nuclear Magnetic Resonance, Differential Scanning Calorimetry and Broadband Dielectric Spectroscopy studies about synthesized hyperbranched polymers of different molecular architecture showed different patterns of behavior due to the effect of the molecular architecture on monomers tacticity along the molecular brushes. Highlights: Well defined hyperbranched polymers of different molecular architecture. Effect of molecular architecture on monomers tacticity along the molecular brushes. Dielectric spectroscopy revealed different patterns of behavior of hyperbranched polymers of different architectures.